Progress in the Application of Food-Grade Emulsions - Yilin Jie; Fusheng Chen (Foods, 2022)
The detailed investigation of food-grade emulsions, which possess considerable structural and functional advantages, remains ongoing to enhance our understanding of these dispersion systems and to expand their application scope. This work reviews the applications of food-grade emulsions on the dispersed phase, interface structure, and macroscopic scales; further, it discusses the corresponding factors of influence, the selection and design of food dispersion systems, and the expansion of their application scope. Specifically, applications on the dispersed-phase scale mainly include delivery by soft matter carriers and auxiliary extraction/separation, while applications on the scale of the interface structure involve biphasic systems for enzymatic catalysis and systems that can influence substance digestion/absorption, washing, and disinfection. Future research on these scales should therefore focus on surface-active substances, real interface structure compositions, and the design of interface layers with antioxidant properties. By contrast, applications on the macroscopic scale mainly include the design of soft materials for structured food, in addition to various material applications and other emerging uses. In this case, future research should focus on the interactions between emulsion systems and food ingredients, the effects of food process engineering, safety, nutrition, and metabolism. Considering the ongoing research in this field, we believe that this review will be useful for researchers aiming to explore the applications of food-grade emulsions.